2019
DOI: 10.1186/s12967-019-1921-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in FTO and IRX3 gene expression in obese and overweight male adolescents undergoing an intensive lifestyle intervention and the role of FTO genotype in this interaction

Abstract: Background Lifestyle intervention may have a critical effect on the association between genetics and obesity. This study aimed to investigate changes in FTO and IRX3 gene expression in obese and overweight male adolescents undergoing a lifestyle intervention and the role of FTO genotype in this interaction. Methods This study was a field trial of 62 adolescents from boys’ high schools in Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…Data are expressed as mean ± SEM of the fold change at 10 and 90 mins compared to pre-exercise measurements (set arbitrarily to 1). 'a' represents significant main effect for time (p < 0.05) FTO genotype was considered, FTO expression was upregulated in AA genotype carriers and down-regulated in AG/GG genotype carriers in the intervention group [29]. Though the direction of FTO mRNA change was opposite to the present study observations, different cell type, age, sex and intervention period, may explain such differences.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Data are expressed as mean ± SEM of the fold change at 10 and 90 mins compared to pre-exercise measurements (set arbitrarily to 1). 'a' represents significant main effect for time (p < 0.05) FTO genotype was considered, FTO expression was upregulated in AA genotype carriers and down-regulated in AG/GG genotype carriers in the intervention group [29]. Though the direction of FTO mRNA change was opposite to the present study observations, different cell type, age, sex and intervention period, may explain such differences.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have shown that FTO gene activity is nutritionally regulated with high fat diet, fasting and glucose ingestion all having effects on FTO mRNA levels [26][27][28]. Only one other study has investigated the effect of high intensity training on FTO mRNA expression and showed lifestyle changes (diet and exercise) did not impact FTO gene expression in peripheral blood mononuclear cells [29]. However, when Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that FTO gene activity is nutritionally regulated with high fat diet, fasting and glucose ingestion all having effects on FTO mRNA levels [26][27][28]. Only one other study has investigated the effect of high intensity training on FTO mRNA expression and showed lifestyle changes (diet and exercise) did not impact FTO gene expression in peripheral blood mononuclear cells [29]. However, when FTO genotype was considered, FTO expression was up-regulated in AA genotype carriers and downregulated in AG/GG genotype carriers in the intervention group [29].…”
Section: Discussionmentioning
confidence: 99%
“…Only one other study has investigated the effect of high intensity training on FTO mRNA expression and showed lifestyle changes (diet and exercise) did not impact FTO gene expression in peripheral blood mononuclear cells [29]. However, when FTO genotype was considered, FTO expression was up-regulated in AA genotype carriers and downregulated in AG/GG genotype carriers in the intervention group [29]. Though the direction of FTO mRNA change was opposite to the present study observations, different cell type, age, sex and intervention period, may explain such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that lifestyle modifications, including personalized diet and physical activity intervention, may impact on obesity through changes in the expression level of the FTO and IRX3 genes. However, this effect is mediated by the genotype of FTO, which is capable of modulating the impact of lifestyle changes on its own expression [68]. These findings have highlighted how important gene variants related to nutrients and metabolism are, especially in terms of a possible link between dietary intake and gene expression and their related functions [69].…”
Section: Future Perspectivesmentioning
confidence: 99%